Securing Underwater Wireless Sensor Networks: A Review of Attacks and Mitigation Techniques - Ahmed, Khawaja Masood; Shams, Rehan; Khan, Fozia Hanif; Luque-Nieto, Miguel Ángel (IEEE, 2024)
In recent years industry’s pursuit of Underwater Wireless Sensor Networks (UWSN) has surged because of UWSN’s advancements in commercial and military applications as well as monitoring marine life. Owing to its capabilities, open acoustic channel, and hostile undersea environment, additionally, it is susceptible to many different types of malicious attacks and threats. Although secure interaction and communication is necessary for many UWSN-based applications, attackers can readily exploit vulnerabilities to steal data while the application is in use. However, most of UWSN research to date has not taken security into account. Due to these factors, the objective of this research is to present a thorough review of UWSN security by going over security requirements as well as the primary UWSN security threats according to layered classification. This paper discusses different security concerns and examines countermeasure schemes against UWSN security attacks and strategies created specifically for UWSNs that discuss several security issues. The aim of this study is to discuss various security concerns and examines countermeasure schemes against UWSN security attacks and strategies created specifically for UWSNs that discuss several security issues. The goal of this study is to recommend future lines of inquiry for UWSN research. The proposed study discusses different strategies that had already addressed the security issues. However, how these schemes are still lacking in the performance and what countermeasures can be considered by different techniques such as confidentiality, integrity, authenticity and many more, in order to fulfill the security issues in under water sensors networks. The goal of this study is to recommend future lines of inquiry for UWSN research. Comparisons of different techniques in terms of energy efficiency, latency, and detection accuracy with other major factors have also been done as a guideline for new research.
Keywords: Redes de sensores inalámbricas; Underwater wireless sensor networks (UWSNs); Security attacks; Attack mitigation; Security mechanism